Computational thermodynamics of materials - Liu, Zi-Kui (Cambridge University Press, 2016)
Includes worked examples, case studies, and end-of-chapter problems, this unique book offers an unrivalled and in-depth understanding of the computational-based thermodynamic approach and how it can be used to guide the design of materials for robust performances. --